Religious Messages in Rapa’i Tuha Aceh Song Lyrics - Ayu Agustya, Kembang; Utomo, Udi; Triyanto, Triyanto (Catharsis, 2020)
Rapa’i Tuha music comes from Aceh, there are many religious messages conveyed through song lyrics. The purpose of this study was to analyze the religious messages contained in the lyrics of the Rapa’i Tuha Aceh music song. This research used a communication approach using qualitative research methods. Data collection techniques were using observation, interviews and documentation. Data analysis procedures were carried out through data reduction, presentation and verification. Data validity used triangulation of data sources, methods and theories. Analysis of religious messages in song lyrics in Rapa’i Tuha music used communication analysis by Effendy, namely the presence of messages and communicators, recipients of messages and the presence of media. The results of this study indicated that the Rapa’i Tuha contains religious messages namely the message of faith and the message of morals. Specifically, the findings in this study were that there was a message of faith which means everything that should be trusted, believed and faithful as a Muslim. As well as moral messages which are reflected in the behavior patterns of our fellow human beings where all of these religious messages are contained in song lyrics in Rapa’i Tuha Aceh music.